ANALISIS NILAI KETAUHIDAN PADA KITAB AQIDATUL AWAM DALAM MENINGKATKAN KETAQWAAN DI PONDOK PESANTREN HIDAYATUL MUBTADI’IN - Afifah Aris Minanti; Amir Mukminin; Zamzam Mustofa (Al-Miskawaih, 2023)
The value of monotheism has a big influence on the level of the quality of a person's piety. This cannot be denied in the life of a Muslim, including a santri. Today, there are so many students who ignore the matter of piety which certainly has a big impact on their future lives. In response to this, Islamic boarding schools provide more intensive learning of the value of monotheism through the book Aqidatul Awam written by Sayyid Ahmad Marzuqi. This book is a basic book in learning the value of monotheism for lay people. The purpose of this study is to examine more deeply how the value of monotheism can increase the level of piety of a student so that the true value of monotheism can lead to a better life than before. In the implementation, the researcher uses qualitative research methods. Qualitative research method is a method that prioritizes process and meaning, not results. As for data collection, the researcher used triangulation technique which is a technique by combining observation, interview and documentation techniques. The type of research approach used is a case study conducted at the Hidayatul Mubtadi'in Islamic Boarding School. Meanwhile, the data analysis in this research is inductive which follows the concept of Miles and Huberman. The results obtained are that through learning the value of monotheism in the book of Aqidatul Awam, it can grow one's faith, where this faith has a major influence on the self-taqwa of a santri, especially at the Hidayatul Mubtadi'in Islamic Boarding School, Ponorogo.